PEMBERDAYAAN KELUARGA DALAM PERAWATAN PENDERITA DIABETES MELITUS DI WILAYAH KERJA PUSKESMAS NGRANDU KABUPATEN PONOROGO - Gandes Widya Hendrawati; Agung Eko Hartanto; Yustina Purwaningsih (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2022)
The increase in the number of non infectious diseases has brought changes in disease patterns from infectious diseases to non infectious diseases. One of the non infectious diseases whose number is increasing is Diabetes Mellitus (DM). The role of the family is very necessary because the family is the main companion and nurse while people with DM are at home. Families can play a role in providing and monitoring diet, monitoring discipline in eating patterns, monitoring activity and exercise, monitoring treatment regimens and monitoring for signs of complications. Counseling was given to 10 families with DM in Sukosari Village, the working area of ??the Ngrandu Ponorogo Health Center. Implementation of counseling by visiting the home of DM patients. Before being given counseling, the majority (60%) lack of knowledge and ability of the family. And after being given counseling, the knowledge and ability of the family in caring for DM patients became all good (100%). Increased knowledge and abilities are obtained because counseling with exposure and training methods is easier to understand. In addition, it is supported by enthusiastic family factors in counseling on the grounds that they want their families to be healthy and there are no complications.